The sense of self and interpersonal functioning in borderline personality disorder: toward qualitative evidence-based phenomenological conceptualization - Sterna, Anna; Fuchs, Thomas; Moskalewicz, Marcin (Qualitative health research, 2025)
Borderline personality disorder (BPD) is typically conceptualized as a disturbance of self-experience. Recent dimensional shift in diagnosis validates the need for conceptual clarity and nuanced understanding of self-impairments. However, these impairments are often examined in isolation from relational contexts, resulting in overly static depictions. A phenomenological approach, focusing on lived experience, offers deeper insight into how self, others, and time interrelate in BPD. This study involved 24 hospitalized individuals with BPD (aged 18-29, 83.3% female) who were interviewed using a modified Life Story Interview. We employed a data-driven, inductive, phenomenological thematic analysis to explore the structure of BPD narrative identity. Two superordinate themes emerged as constituting the core of BPD narrative identity: self and the other. Self-experience is marked by identification with one's harmful past, a sense of disconnected present identities, and anticipated unpredictability. Complementarily, the experience of others revolves around a felt sense of ever-present and anticipated hostility, the overintensity of intimacy, and the influence of others on one's self-experience. This indicates that self- and other-experience are inherently linked, co-creating recurrent dynamics that hinder one's development. Lived-experience data illuminate the close-cycled, past-devoted temporal dynamics of self and interpersonal functioning. BPD narrative identity appears paradoxically rigid in terms of its unchanging self- and other-processing patterns, even though its explicit manifestation seems highly changeable. This reveals a diminished capacity for self-transcendence and active self-modification, which may disclose mechanisms underlying symptom maintenance. Incorporating subjective accounts of self and interpersonal functioning may enhance the accuracy of diagnostic criteria and improve their clinical utility.